Gambaran Pengetahuan Kanker Serviks di Kecamatan Sawangan Kota Depok - Boenga NurCita; Melly Kristanti (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Cervical cancer ranks second with 36,633 cases or 9.2% of total cancer cases. The factor that causes delays in early detection of cervical cancer diagnosis is due to the lack of public knowledge related to cervical cancer which is still relatively low. This cancer is found in women aged between 25-34 years with a peak at the age of 45-54 years due to late diagnosis. This study aims to see a picture of cervical cancer knowledge in Depok City in 2023 as an early prevention effort. The study design of this study is cross sectional with a total of 30 samples. The sampling technique is purposive sampling. Data analysis of this study used chi-square. The results showed that there was a significant relationship between education with p-value knowledge 0.043, occupation with p-value knowledge 0.374 and marital status with p-value knowledge 0.197. The characteristics of respondents are the average age of 35 years with the most education, namely Strata 1 and above, which is 60% and high knowledge 53.3%. A person's knowledge is related to the educational status they have so it needs to be paid more attention to in providing cervical cancer counseling.